ANALISIS DAMPAK PEMEKARAN DESA TERHADAP PEMBANGUNAN INFRASTRUKTUR DI DESA SUNGAI BENDUNG AIR KECAMATAN KAYU ARO: H. EDWIN BUSTAMI, SE., MM - Edwin Bustami (LPPM STIA Nusantara Sakti, 2018)
This study took place in the village of Sungai Bendung Air, Kayu Aro Subdistrict, Kerinci Regency, the purpose of this study was to determine the impact of village division on infrastructure development in Sungai Bendung Air village, Kayu Aro sub-district. The research method used is a descriptive study that provides information about division in Sungai Bendung Air Village. In general, descriptive research activities include data, data analysis, data interpretation and conclude with a conclusion on the data analysis.The informants in this study amounted to 14 people, data collection techniques and tools in this study were interviews, observation, documentation, data collection tools in the form of questionnaires, books / papers. The unit of analysis is the village government and the community of Sungai Bendung Air village.Based on data analysis from the results of interviews conducted, it was concluded that village division had a good impact in accelerating infrastructure development in Sungai Bendung Air village, this could be seen from the physical developments that existed after village division such as road construction, posyandu, building halls, PAMDes and development BUMDes in the tourism sector. The success of this development certainly cannot be separated from the enthusiasm and cohesiveness of the community with the village government in order to realize the prosperity of the community of Sungai Bendung Air.